Management of palatal defect post hemimaxillectomy: a case report - Pra Purnama Ramadhan; Ike Damayanti Habar; Eri Hendra Jubhari; Imran Irsal; Irsal Wahyudi Sam (Indonesian Journal of Prosthodontic, 2022)
A 42-year-old woman was referred to the Department of Prosthodontics, Hasanuddin University Dental Hospital with speech, swallowing and chewing difficulties caused by a fractured and non-reusable acrylic obturator. The patient had been using the obturator since maxillary tumor resection in 2012, which resulted in a significant and deep defect in the right maxillary region. Intraoral examination revealed a defect in the midline of the palate that extended to the left alveolar bone, and 21, 22, 23, 24, 25, 26, 27, 16 were edentulous. The maxillary defect did not appear inflamed or infected, and the surrounding area appeared normal. The treatment plan was fabrication of a maxillofacial skeletal partial denture to rehabilitate the maxillary defect. Primary impressions were made with irreversible hydrocolloid ma-terial with a stock tray to obtain a study model. Custom tray was made for individual impressions with polyvinyl si-loxane material to obtain working models. A survey was conducted, and framework and bite rim were made. Maxil-lary denture was designed with Akers clasps at 35, 37, RPI at 45, full palatal palate as main connector. The denture framework was tried on, followed by determination of vertical dimensions. Denture alignment was done in the articu-lator using A3 color. The was prostheses were tried in and evaluated of retention, articulation, phonetics, and aes-thetics; then sent to dental laboratory for processing and the obturator was then inserted into the patient's mouth. Pati-ent follow-up was scheduled 24 hours and 1 week after insertion. It is concluded that the maxillofacial partial den-ture is a rehabilitation device that can result in decent retention and stabilization, especially in cases of acquired de-fects. The prosthesis can improve patient adaptation and ability with speech, mastication and swallowing functions.